Comprehensive study of Mn–Fe–Al oxygen-carriers for chemical-looping with oxygen uncoupling (CLOU). (March 2015) - Azimi, Golnar; Mattisson, Tobias; Leion, Henrik; Rydén, Magnus; Lyngfelt, Anders
Highlights: Addition of Al2 O3 to materials with Mn:Fe molar ratio of 80:20 was not advantageous. Addition of Al2 O3 to materials with Mn:Fe molar ratio of 33:67 was advantageous. They showed good attrition resistance. They showed good reactivity with methane, syngas and char. They have low raw materials costs which make these materials interesting for CLC. Abstract: The reactivity and attrition resistance of Mn–Fe oxygen carriers with addition of Al2 O3 as support have been investigated. Spray-dried oxygen-carrier particles with Mn:Fe molar ratios of 80:20 and 33:67 were prepared using different amounts of Al2 O3 . Each material was calcined for 4 h at 950 °C, 1100 °C or 1200 °C. The oxygen carriers were studied in a batch fluidized bed reactor to investigate their reactivity with wood char, CH4, syngas and also their oxygen release in N2 . In order to measure the mechanical stability of the different materials, the attrition resistance was measured in a jet-cup apparatus. Addition of Al2 O3 to materials with a Mn:Fe molar ratio of 80:20 was not advantageous. Generally oxidation of these materials was problematic. The Al2 O3 supported materials with a Mn:Fe molar ratio of 80:20 calcined at 950 °C and 1100 °C showed poor attrition resistance and were highly fragmented or turned to dust, whereas those calcined at 1200 °C showed high attrition resistance but poor gas conversion.Materials with a Mn:Fe molar ratio of 33:67 supported with Al2 O3 generally showed better attrition resistance. Also their oxidation with 5 vol% of oxygen was possible at temperatures higher than 850 °C. Furthermore, some of these materials showed good reactivity with methane, syngas and char. Low attrition, good reactivity and CLOU properties in combination with potentially low raw materials costs, make these materials interesting for CLC.